(untitled) (Journal Of Educational and Psychological Researches, 2025)
The current research aims to identify the level of psychological empowerment and the level of enjoyment of life among school teachers, as well as identify the significance of the statistical difference in psychological empowerment and enjoyment of life among school teachers in terms of gender. The research also aims to examine the relationship between psychological empowerment and enjoying life among school teachers. The researcher adopted the Psychological Empowerment Scale of 12 items designed by Spritzer (1995), which was translated into Arabic by Al-Nawajah (2015) and distributed over four domains: meaning, competence, choice, and influence. He also adopted the enjoyment life scale of 31 items designed by Jassem and Mahmoud (2021), which was distributed over three domains: happiness, satisfaction, and personal well-being. The scale was applied to a sample of 200 male and female primary school teachers in Baghdad Governorate for the academic year 2023-2024. The results revealed that the sample of research has a low level of psychological empowerment and enjoyment of life. There are also differences between males and females in favor of males regarding psychological empowerment and enjoyment of life. Moreover, there is a direct relationship between psychological empowerment and enjoyment of life among school teachers. In light of the results, the researcher presented several recommendations and suggestions.